Предмет: Алгебра,
автор: kristinpolenkop3di99
СРОЧНО!!!!!(ответы скорее всего 1;2;10)ОТДАЮ ВСЕ БАЛЛЫ
Приложения:

Ответы
Автор ответа:
1
!!!!!!!!!!!!!!!!!!!!!!!!
Приложения:

kristinpolenkop3di99:
Спасибо!!!!
Автор ответа:
1
∛(2-x)= 1-√(х-1)
(∛(2-x))³ =( 1-√(х-1))³
2-x= 1³ - 3√(х-1)+ 3√(х-1)²- √(х-1)³
1 -x= - 3√(х-1)+ 3х- 3 -√(х-1)³
4(1 - x) = - 3√(х-1) - (х-1)√(х-1)
4(1 - x) + 3√(х-1) +(х-1)√(х-1)=0
√(х-1)* (4√(х-1)+3 +(х-1) )= 0
√(х-1)* (4√(х-1)+2 +х- )= 0
√(х-1)=0 x₁=1
4√(х-1)+ 2 + х=0
4√(х-1)= - 2 - x
(4√(х-1))²=( - 2 - x)²
16(х-1)= 4+4x+ x²
16х-16= 4+4x+ x²
x²-12x+20=0
D= 144-80=64
x₂=(12+8)/2=10
x₃=(12-8)/2= 2
Похожие вопросы
Предмет: Физика,
автор: artemsaacenko3
Предмет: Математика,
автор: alex2002www
Предмет: Математика,
автор: tanazribnaa
Предмет: Физика,
автор: pashakuzmench
Предмет: История,
автор: MrBoba98